Standard of prevention for infectious diseases' prevention clinical trials during pandemics: learning lessons for global policies from biomedical HIV prevention clinical trials and a case study of COVID-19 - Foláyan, Moréniké Oluwátóyìn; Dubé, Karine; Ndembi, Nicaise (Frontiers in Public Health, 2025)
Lessons from biomedical HIV prevention research indicate that standard of prevention packages evolve over time, and require active engagement of stakeholders and community advocates to define packages accept to community members and trial participants. Using COVID-19 prevention research as an example, this paper discusses the reasons why a standard of prevention package must be defined for infectious diseases prevention research, what the minimum content of this package may be, the importance of stakeholder engagement in defining the package, the role of the government, and ethical considerations. As the experience from the HIV pandemic had shown, multiple ethics guidelines argue for a comprehensive standard of prevention package for biomedical HIV prevention trials that does not preclude the inclusion of newly developed HIV prevention tools including those experimental products listed for emergency use during health crisis. In the case of COVID-19, the standard of prevention package should include at a minimum, risk reduction counseling on physical distancing, provision of hand sanitizers, education on how to use available prevention tools, and provision for the possibility of vaccine-induced seropositivity. When pre-exposure prophylaxis studies are conducted for healthcare workers and home carers, personal protective equipment should be provided. Regional and country level regulatory provisions on these issues can provide critical guidance for research design and implementation.